Extracellular Enzyme Activities and Carbon/Nitrogen Utilization in Mycorrhizal Fungi Isolated From Epiphytic and Terrestrial Orchids - Zhao, Zeyu; Shao, Shicheng; Liu, Na; Liu, Qiang; Jacquemyn, Hans; Xing, Xiaoke (Frontiers in Microbiology, 2021)
Fungi employ extracellular enzymes to initiate the degradation of organic macromolecules into smaller units and to acquire the nutrients for their growth. As such, these enzymes represent important functional components in terrestrial ecosystems. While it is well-known that the regulation and efficiency of extracellular enzymes to degrade organic macromolecules and nutrient-acquisition patterns strongly differ between major fungal groups, less is known about variation in enzymatic activity and carbon/nitrogen preference in mycorrhizal fungi. In this research, we investigated variation in extracellular enzyme activities and carbon/nitrogen preferences in orchid mycorrhizal fungi (OMF). Previous research has shown that the mycorrhizal fungi associating with terrestrial orchids often differ from those associating with epiphytic orchids, but whether extracellular enzyme activities and carbon/nitrogen preference differ between growth forms remains largely unknown. To fill this gap, we compared the activities of five extracellular enzymes (cellulase, xylanase, lignin peroxidase, laccases, and superoxide dismutase) between fungi isolated from epiphytic and terrestrial orchids. In total, twenty-four fungal strains belonging to Tulasnellaceae were isolated and identified. Cellulase and xylanase activities were significantly higher in fungi isolated from terrestrial orchids (0.050 ± 0.006 U/mL and 0.531 ± 0.071 U/mL, respectively) than those from epiphytic orchids (0.043 ± 0.003 U/mL and 0.295 ± 0.067 U/mL, respectively), while superoxide dismutase activity was significantly higher in OMF from epiphytic orchids (5.663 ± 0.164 U/mL) than those from terrestrial orchids (3.780 ± 0.180 U/mL). Carboxymethyl cellulose was more efficiently used by fungi from terrestrial orchids, while starch and arginine were more suitable for fungi from epiphytic orchids. Overall, the results of this study show that extracellular enzyme activities and to a lesser extent carbon/nitrogen preferences differed between fungi isolated from terrestrial and epiphytic orchids and may indicate functional differentiation and ecological adaptation of OMF to local growth conditions.